Characterizing the pre–Space Age ionosphere over Washington, DC. Issue 8 (18th August 2014) - Rice, D. D.; Sojka, J. J.; Eccles, J. V.; Redmon, R.; Hunsucker, R. D.
Abstract The study of long‐term changes requires researchers to identify relevant historical measurements; quantifying and quality controlling these measurements becomes central to their utilization by broader communities. This pilot study reports on the evaluation of ionograms and their inversion from the decade prior to the Space Age. The ionograms were recorded on 35 mm film reels and archived at the National Geophysical Data Center World Data Center A in Boulder, Colorado. For this study, ionogram film from one of the earliest operational sites in North America, Fort Belvoir (near Washington, DC), is analyzed. This analysis generates two distinct products: a digital ionogram with virtual height and frequency coordinate registration, and scaled values including an electron density profile. Validation of the ionogram registration and its resolution are described. The scaling and inversion processing, including uncertainties for the parameters and quality assessment, are explained. This study demonstrates how the archived film ionograms can have extensive value as historic measurements of the ionosphere once they are digitized and coordinate registered. Furthermore, modern analysis of the ionograms shows that a complete bottomside ionospheric specification may be obtained at better time resolution than is typically available from original scaled data. This research has set the stage for an effective recovery of ionospheric information for almost a full solar cycle prior to International Geophysical Year. In addition, between Fort Belvoir and Wallops Island archives, an East Coast midlatitude ionospheric data set can be generated from the late 1940s through the present.